2016
DOI: 10.1371/journal.pone.0143942
|View full text |Cite
|
Sign up to set email alerts
|

Grey Matter Atrophy in Multiple Sclerosis: Clinical Interpretation Depends on Choice of Analysis Method

Abstract: BackgroundStudies disagree on the location of grey matter (GM) atrophy in the multiple sclerosis (MS) brain.AimTo examine the consistency between FSL, FreeSurfer, SPM for GM atrophy measurement (for volumes, patient/control discrimination, and correlations with cognition).Materials and Methods127 MS patients and 50 controls were included and cortical and deep grey matter (DGM) volumetrics were performed. Consistency of volumes was assessed with Intraclass Correlation Coefficient/ICC. Consistency of patients/co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 45 publications
4
35
2
1
Order By: Relevance
“…Although lesion filling techniques improve accuracy of tissue segmentation (Chard, Jackson, Miller, & Wheeler‐Kingshott, 2010; González‐Villà et al., 2017), they did not appear to substantially affect measures of whole‐brain volume as we chose to use here (Dell'Oglio et al., 2015). There is an extensive literature regarding the optimization of GM versus WM tissue segmentation postprocessing techniques (Derakhshan et al., 2010; Popescu, Schoonheim, et al., 2016; Rocca et al., 2017), which is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although lesion filling techniques improve accuracy of tissue segmentation (Chard, Jackson, Miller, & Wheeler‐Kingshott, 2010; González‐Villà et al., 2017), they did not appear to substantially affect measures of whole‐brain volume as we chose to use here (Dell'Oglio et al., 2015). There is an extensive literature regarding the optimization of GM versus WM tissue segmentation postprocessing techniques (Derakhshan et al., 2010; Popescu, Schoonheim, et al., 2016; Rocca et al., 2017), which is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…MRI‐derived volumetrics are prone to deviations throughout the data pipeline, including at the acquisition stage (e.g., head motion, hardware nonuniformity including magnetic field strength, gradient distortions, and pulse sequence type and parameters; Chu, Hurwitz, Tauhid, & Bakshi, 2017; Papinutto et al., 2017; Sharma et al., 2004; Shinohara et al., 2017) and segmentation procedure (e.g., preprocessing steps—inhomogeneity correction, method of tissue class segmentation, and normalization; Chard, Parker, Griffin, Thompson, & Miller, 2002; Chu, Hurwitz, et al., 2017; Durand‐Dubief et al., 2012; Granberg et al., 2016; Kazemi & Noorizadeh, 2014; Popescu, Schoonheim, et al., 2016; Vidal‐Jordana et al., 2017). Furthermore, brain volume may vary based on pathophysiological factors, including recent start of immunomodulatory therapy, acute inflammation, hydration status, time of day, tobacco use, genetics, and comorbid conditions (Rocca et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of real data also provides an opportunity to qualitatively compare ClusterZ to the popular ALE and the ES-SDM algorithms. The meta-analysis of VBM studies of MS patients revealed some of the clusters that have been demonstrated to be the most consistently atrophied in a recent study comparing software packages for volumetric analysis in relapsing remitting MS [34]. A further example using real data analyses functional studies of healthy controls receiving painful mechanical stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The same two platforms that gave these different results for teriflunomide (brain parenchymal fraction and SIENA) were considered to be the only reliable tools for assessing brain volume in a recent meta-analysis in which all the results from both of them were pooled 57 . If grey matter is the subject of investigation, variations are wide among methods used for analyses 35,36,37 , and several years of follow up may be necessary for conclusions 50 . On the other hand, cortical atrophy in MS occurs largely in a non-random manner and seems to affect distinct anatomical areas 58,59 .…”
mentioning
confidence: 99%